Information Management in the Modern Hydrographic Office - A Challenge for the 21st Century - Burrows, K. G. (The International Hydrographic Review, 2015)
Collectively, the various national hydrographic authorities within the auspices of the International Hydrographic Organization (IHO) are the custodians of a significant portion of the world asset of marine information. In the course of managing this information, Member States have been subject to significant changes in both technology and user requirements. The current practices that have evolved to provide a relatively uniform service of charts and other publications for the international mariner are today under increasing pressure to adapt to a wider variety of specific user needs and the methodologies for presentation. Consideration must be given as to whether the current information management practices in place today are able to meet the source data capabilities and user requirements of tomorrow. This paper discusses a rationale for the structuring that may bë required for future hydrographic information management. It examines current problems and some potential directions in the overall management and organization of the types of information held by the modem hydrographic agency. An appreciation and understanding of the issues surrounding information management in hydrographic organizations, under the auspices of the International Hydrographic Organization, must lead to a closer cooperation towards meeting the challenge of international information dissemination in the twenty-first century.